The entrepreneurship of marginalized groups and compatibility between the market and emancipation - Lewis, Alexander C.; Crabbe, Rowena C. (Journal of Business Venturing, 2024)
This paper offers a market-compatible perspective of the emancipatory entrepreneurship of marginalized groups. We identify two dimensions of market-emancipation compatibility that derive from tensions inherent in the emancipatory entrepreneurship of marginalized groups. Ends-compatibility reflects the misalignment of emancipatory outcomes with market outcomes. Means-compatibility reflects the constraint entrepreneurs from marginalized groups encounter in market structures. We engage with these tensions in the context of the businesses, processes, and products that emerge from the entrepreneurship of marginalized groups. We use these tensions to derive propositions that speak to the likelihood emancipatory opportunities develop and that these opportunities are exploited by marginalized groups. With these propositions, we contribute to debates about entrepreneurship's overall emancipatory capacity. Specifically, we contribute a conceptual space in which the market forces that structure entrepreneurial activity and the material realities of venturing from marginalized social positions are incorporated into theorizing and testing entrepreneurship's capacity to enable marginalized groups with respect to structural disadvantage.